Pertumbuhan dan Produksi Tanaman Seledri (Apium graveolens L.) dengan Aplikasi Nutrisi Organik Melalui Sistem Hidroponik: Growth and Production of Celery Plants (Apium graveolens L.) with the Application of Organic Nutrients Through Hydroponic Systems - Fitrianti Handayani; Fitrah Adelina; Maretik Maretik; Djunarlin Tojang; Essa Annisa Syadiah (Departemen Biologi, Institut Pertanian Bogor, 2023)
Celery plant (Apium graveolens L.) belongs to the class of important leaf vegetables and has export value. Celery is widely grown in Indonesia is leaf celery which has many benefits, among others, can be used as a complement to the cuisine and has medicinal properties. The study was conducted in July-October 2022 in Toari Village, Toari District, Kolaka Regency, Prov. Southeast Sulawesi. This study uses a complete random design (CRD) single factor pattern consisting of 3 (three) treatments, namely BP0 as a control, BP1 with a dose of 200 ml/liter of banana weevil water, BP2 with a dose of 250 ml/liter of banana weevil water so that there are 9 experimental units. Further test using the Least Significance Different (LSD). The parameters observed were plant height, number of leaves, and fresh weight of the plant. The results showed that the treatment of BP2 with a dose of 250 ml/liter of banana tuber water has the highest value compared to the treatment of BP1 and BP0. The results of variety analysis showed that the organic nutrition of banana weevil had a significant effect on plant height, number of leaves, and fresh weight of the plant.